UNJUK KERJA MESIN VERTICAL RAW MILL PLANT 10 - Saputra, Theo Chandra; Koswara, Engkos (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
PT X. is a cement manufacturing company. which experiences production losses due to the high value of downtime. Based on downtime data, the largest machine downtime value is found in the Raw Mill, so the Raw Mill machine becomes the object of research. This study aims to measure the effectiveness of the Raw Mill machine in the application of Total Productive Maintenance (TPM). The method used is Overall Equipment Effectiveness (OEE) to measure machine effectiveness and loss factor analysis with the Six Big Losses method. The results found that the average OEE value in 2022 was below the international OEE standard of 85%, namely 78% for Raw Mill Plant 10 in the 2019 period and 74% in the 2022 period. The low performance of the Raw Mill Plant 10 machine is caused by the breakdown loss factor and the reduced speed loss factor. The root causes found are lack of mechanical training and lack of control for spare parts. The recommendations given are the implementation of predictive maintenance, improving training facilities, and creating a spare parts inventory management system.